2020
DOI: 10.1093/nar/gkaa586
|View full text |Cite
|
Sign up to set email alerts
|

Cutting in-line with iron: ribosomal function and non-oxidative RNA cleavage

Abstract: Divalent metal cations are essential to the structure and function of the ribosome. Previous characterizations of the ribosome performed under standard laboratory conditions have implicated Mg2+ as a primary mediator of ribosomal structure and function. Possible contributions of Fe2+ as a ribosomal cofactor have been largely overlooked, despite the ribosome's early evolution in a high Fe2+ environment, and the continued use of Fe2+ by obligate anaerobes inhabiting high Fe2+ niches. Here, we show that (i) Fe2+ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…In sum, the effects of Mg 2+ on RNA persistence are expected to be pleomorphic, both protecting and degrading RNA. Folding is typically fast (28–32) compared to Mg 2+ -catalyzed cleavage (3, 5, 6), so cleavage operates over a fixed fold landscape.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, the effects of Mg 2+ on RNA persistence are expected to be pleomorphic, both protecting and degrading RNA. Folding is typically fast (28–32) compared to Mg 2+ -catalyzed cleavage (3, 5, 6), so cleavage operates over a fixed fold landscape.…”
Section: Resultsmentioning
confidence: 99%
“…RNA is especially fragile. In-line attack by 2'OH groups on adjacent phosphates catalyzes RNA cleavage (2)(3)(4) in reactions accelerated by divalent cations (5)(6)(7)(8). However, divalent cations also promote folding of RNAs (9-13), and are generally required for catalytic function of ribozymes (14)(15)(16), and for RNA biosynthesis (17), and RNA processing by protein enzymes (18).…”
Section: Introductionmentioning
confidence: 99%
“…This is because some models predict reducing, circumneutral, and cool conditions throughout the Hadean (Charnay et al., 2017; Kadoya et al., 2020). Specifically, studies have demonstrated that Fe 2+ may have preceded life's transition to Mg 2+ due to its versatility in catalyzing polymerization (e.g., Jin et al., 2018), ribozyme folding (Athavale et al., 2012), translation (Petrov et al., 2015), and imparting novel catalytic activity (Guth‐Metzler et al., 2020; Hsiao et al., 2013; Okafor et al., 2017). It is therefore conceivable that Fe 2+ could have had a comparable influence on the stability, polymerization, and function of RNA on early Mars and should accordingly be discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Since ascorbic acid can act as a pro-oxidant in addition to acting as an antioxidant, we considered that an increase in pro-oxidant activity could contribute to increased translation repression. A reaction between iron and ascorbic acid can generate hydrogen peroxide, increasing oxidative stress and leading to cleavage of the 25s rRNA in the 60s ribosomal subunit (Zinskie et al, 2018;Guth-Metzler et al, 2020;Kazmierczak-Barańska et al, 2020). If this reaction was occurring, it could explain the accumulation at the 40s peaks in the ascorbic acid polysome profiles.…”
Section: A Putative Gcn4 Ortholog Connects Methionine Utilization Andmentioning
confidence: 99%